Water matters : achieving the sustainable development goals - Mukherjee, Abhijit (Elsevier, 2024)
"Water Matters: Achieving the Sustainable Development Goals presents a compilation of water scenarios and their relationship to multiple facets of life, as water forms a nexus with food security and energy resources, thereby forming one of the fundamental pillars of sustainable development. The thematic topics focus on studies of achieving individual sustainable development goals looking through the lens of water availability and usage, ranging from safe and sustainable drinking water availability to poverty alleviation, inequalities, climate change, and solutions for future. Each chapter presents holistic review of the topic and provides insight for further research, along with a case study of the specific theme. This book integrates the knowledge on global-scale water reviews to local-scale case studies, ideal for hydrologists, hydrogeologists, and water managers in earth and environmental sciences, social sciences, and economics."--